ESTIMATING AND RECYCLING OF CONSTRUCTION DEBRIS IN BASRAH GOVERNORATE - Hassan, Abdulameer Qasim (Basrah Journal for Engineering Sciences, 2014)
The problem of construction debris has been emerged as one of the most important environmental problems in the Iraqi governorates due to higher rates of population growth and the need for the establishment of new construction projects to rebuilding Iraq. Therefore, this research aims to estimate the quantity of construction debris in Basra governorate and suggested method for recycling the homogeneous to rubble material that can be used in the building after admixing with cement. The study estimated the quantity of this debris in Basra during the study period, amounting to a full year up to 177.907 tons, that is equivalent to an average of 0.06 tons/m². And recycling of debris concrete to give the results of the usual approach to the concrete and be within the limits allowed in the code of Iraq and the U.S. and can be used in the production of non-loading concrete blocks.